Expression and implication of osteopontin in renal cortex of diabetic rats - Cao, Yan-Ping (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2008)
OBJECTIVE: To investigate the expression and implication of osteopontin (OPN) in renal cortex of diabetic rats